2010
DOI: 10.1007/s00441-010-0987-3
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of parental genomes in embryonic stem cell/fibroblast hybrid cells depends on the ploidy of the somatic partner

Abstract: Two dozen hybrid clones were produced by fusion of diploid embryonic stem (ES) cells positive for green fluorescent protein (GFP) with tetraploid fibroblasts derived from DD/c and C57BL-I(I)1RK mice. Cytogenetic analysis demonstrated that most cells from these hybrid clones contained near-hexaploid chromosome sets. Additionally, the presence of chromosomes derived from both parental cells was confirmed by polymerase chain reaction (PCR) analysis of polymorphic microsatellites. All hybrid cells were positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
2
4
0
1
Order By: Relevance
“…These events can be considered as the first steps in the bilateral reprogramming of both ES cell/fibroblast heterokaryons. These data are consistent with the findings that the acquisition of the characteristics of the dominant genome and the inhibition of the characteristics of the non-dominant genome by heterokaryons can be manifested without cell division (Blau et al 1983;Terranova et al 2006;Han et al 2008;Sumer et al 2008;Pereira et al 2008;Palermo et al 2009;Kruglova et al 2010). Moreover, the extinction of fibroblast-specific gene expression is also considered as the first event in the reprogramming of fibroblasts under effects of the exogenous expression of defined transcription factors in the generation of induced pluripotent stem cells (Mikkelsen et al 2008;Stadtfeld et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…These events can be considered as the first steps in the bilateral reprogramming of both ES cell/fibroblast heterokaryons. These data are consistent with the findings that the acquisition of the characteristics of the dominant genome and the inhibition of the characteristics of the non-dominant genome by heterokaryons can be manifested without cell division (Blau et al 1983;Terranova et al 2006;Han et al 2008;Sumer et al 2008;Pereira et al 2008;Palermo et al 2009;Kruglova et al 2010). Moreover, the extinction of fibroblast-specific gene expression is also considered as the first event in the reprogramming of fibroblasts under effects of the exogenous expression of defined transcription factors in the generation of induced pluripotent stem cells (Mikkelsen et al 2008;Stadtfeld et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…This point is very important because after the fusion of ES cells and fibroblasts, hexaploid hybrid cells with 1:2 parental genome ratios are often formed, and the partner that introduces two copies of the genome ultimately defines the hybrid cell phenotype. Consistently, in a previous study, we demonstrated that the fusion of mouse tetraploid fibroblasts with diploid mouse ES cells generated hybrid cells with a fibroblast-like phenotype only 13 . Hence, we cannot exclude the likelihood that hybrid cells with fibroblast-like phenotypes were formed from the fusion of two fibroblasts and one ES cell.…”
Section: Introductionsupporting
confidence: 91%
“…ESCs and iPSCs were cultured on disks of Melinex polyester film (175 μm thickness; Agar Scientific; Kruglova et al, 2010) and remained attached to the Melinex film during all treatments and embedding. Initial fixation of the cells was performed for 15 min with 2.5% glutaraldehyde in the culture medium, and then the cells were postfixed with 2.5% glutaraldehyde in 0.1 M sodium cacodylate buffer (pH 7.3) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%